Design of an inductor-based DC/DC buck converter - Abdul Hafiz Surani (Nanyang Technological University, 2019)
The aim of this project is to design a dc-dc buck converter. The design will focus on the synchronous buck with voltage-mode control feedback to regulate the output voltage. The buck converter is designed and implemented with the use of 0.18μm CMOS process technology and simulated on the Cadence software. The report will cover the background knowledge of buck converter and the design process of the components as well as validation of the design for each component and the overall system through simulations.